Abnormal Programmed Cell Death of Tapetum Leads to the Pollen Abortion of Lycium barbarum Linnaeus - Xin Zhang; Zhanlin Bei; Haijun Ma; Zhaojun Wei; Jun Zhou; Yufeng Ren; Wendi Xu; Peng Nan; Yuguo Wang; Linfeng Li; Wenju Zhang; Ji Yang; et al. (Horticulturae, 2022)
Programmed cell death (PCD) in tapetum provides nutrients for pollen development. Once this process becomes abnormal, the pollen will be aborted, and sterile lines will be formed. Lycium barbarum L. is a well-known medicinal and edible plant, and male sterile lines play an important role in the cultivation of its new varieties by utilizing hybrid vigor. However, the male sterility mechanism of L. barbarum is poorly understood. In this study, the main characteristic changes during the pollen development of L. barbarum sterile line (Ningqi No. 5) and fertile line (Ningqi No. 1) were compared through anatomical observation, physiological detection and gene expression analysis. Anatomical observation showed that compared with that of the fertile line, the tapetum of the sterile line persisted during pollen development, the organelle morphology and number of tapetal cells changed remarkably, and the PCD was remarkably delayed. Membranous peroxidation caused by reactive oxygen species (ROS) in the sterile line occurred from the late tetrad to the pollen grain stage, and that in Ningqi No. 1 transpired in the tetrad stage. This difference in the dynamic changes of ROS affected the redox balance of microspore development. qPCR detection of DYT1 and MS1 genes regulating tapetum development showed that compared with those in the fertile line, the expression levels of both genes in the sterile line changed significantly from pollen mother cell stage to pollen grain stage. This finding may be associated with the start-up delay of tapetal PCD. All these results suggested that abnormal tapetal PCD is an important mechanism leading to male sterility in L. barbarum.